Git and GitHub Application Training Program to Support Vocational High School Students in Collaborative Computer Programming Learning - Herlambang, Admaja Dwi; Rachmadi, Aditya; Wijoyo, Satrio Hadi (JPPM (Jurnal pendidikan dan pemberdayaan masyarakat), 2023)
The training program aims to improve students’ ability to operate the Git/GitHub application in collaborative computer programming learning. The partners who are the subject of training activities are three Vocational High Schools of the Computer and Informatics Engineering Expertise Program (SMK TKI) in Malang City and Batu City, East Java Province, Indonesia. The training program was developed with the ASSURE model. The learning strategy used by the training team is peer-to-peer learning. Each vocational school determines 40 students as participants in the training program. Training activity success data were collected using knowledge tests, performance tests, self-evaluation sheets, and questionnaires. The analysis design uses One-Group Pretest-Posttest. The data were analyzed with the One Sample T-test technique. The Posttest value (M=74.88; SD=6.68) is higher than the pretest (M=46.62; SD=9.28). One Sample T-test analysis on the Pretest and Posttest scores yielded t(119)=26.28; p 0.01; d=3.50. The Pretest score significantly differs from the Posttest score, where the effect size score is 3.50, and the p-value is smaller than 0.05 (α).